Characteristics of Small-Scale Coastal Fisheries in China and Suggested Improvements in Management Strategies: A Case Study From Shengsi County in Zhejiang Province - Xiong, Minsi; Wu, Zuli; Tang, Yi; Su, Shu; Shen, Huihui (Frontiers in Marine Science, 2022)
Small-scale fisheries (SSFs) in China have made incalculable contributions to the supply of aquatic products, employment, and social stability. Despite their importance, aspects such as the complexity, dynamicity, and vulnerability of SSFs are yet to receive sufficient attention either from the Chinese government or from society. Here we help to address the lack of recognition of SSFs by examining their characteristics and possible management solutions. We selected Shengsi County, a community with traditional fishing activities, in Zhejiang Province as a case study to review and examine the SSFs’ characteristics and policies. We aimed to explore the improvement strategies for Chinese SSF management by using data from the open-access government databases, a series of questionnaire surveys and semi-structured interviews, and a collection of national and local SSF-related legislative and policy documents. Here we summarized the physical characteristics of the small-scale fishing vessels and the socioeconomic aspects of SSFs in Shengsi County. Our findings indicate that unprecedented new institutional arrangements for SSFs have been developed in recent years at the national level, and some relevant policies of SSFs also exist at the local level. However, there are still gaps: The concept of SSFs and the goal of their management have not been developed either at the national or local levels; monitoring systems have not yet been established for collecting SSF-related data; fishers engaged in SSFs are still not well organized; cooperation and coordination between different government departments with management authority over SSFs are insufficient; the local government’s response to the central government’s initiatives was slow. Our findings show that the Chinese government could improve SSF management by adopting on an ongoing basis the following suggestions: (1) better define SSFs and set management goals according to their characteristics; (2) develop a monitoring system for SSFs’ data and information collection and promote multidisciplinary research on SSFs; (3) establish SSFs’ cooperatives as soon as possible; and (4) develop coordination and cooperation mechanisms among government departments. This research can provide a reference for the Chinese government to understand SSFs better and contribute to the implementation and improvement of SSFs’ differentiated management in China.